One-way ANOVA model to study whole-body vibration attributes among taxi drivers – An emphasis on the role of speed. Issue 1 (March 2018) - Derakhshanjazari, Milad; Monazzam, Mohammad Reza; Hosseini, Seyed Mostafa; Poursoleiman, Mohammad Saeid
Taxi drivers are daily exposed to frequent and prolonged whole-body vibration. This can cause complications such as back pain among them. Since the vibration level depends on many factors, the present study was performed to model the impact of vehicle speed on the attributes of whole-body vibration among the Peugeot 405 taxi drivers. In this experimental study, the whole-body vibration was measured while other variables including tire pressure, engine speed, road gradient, number of passengers, and type of tire, springs, and shock absorbers had been fixed. The measurements were done according to ISO2631–1 at different speeds of 20, 40, 60, and 80 km/h. Increasing the vehicle speed caused an increase in the average value of vibration attributes including Z-axis (vertical) r.m.s. acceleration, 8-h equivalent acceleration, vibration dose value (m/s 1.75 ), and crest factor (P < 0.05). At the speed of 80 km/h, the average vibration dose value (17.6 m/s 1.75 ) exceeded the upper limit of the ISO 2631–1:1997 health caution zone (>17). Further, 8-h equivalent acceleration, at the speeds of 60 and 80 km/h, was beyond the upper limit (>0.9 m/s 2 ). According to the crest factor, increasing speed would cause greater vibration peaks along the Z-axis (worst-case axis). The amount of whole-body vibration is sensitive to speed changes so that urban taxi drivers who are usually driving at low speeds for inner-city transits will be exposed to a lower average value of whole-body vibration. Due to the evident effect of speed on whole-body vibration attributes, it is strongly recommended to be given full consideration to this factor in preparing vibration control plans for vehicles.